The Effects of Nitrogen sources in the concentrates on N utilization and production performances of dairy goats - Asih, A Rai Somaning; Wiryawan, I Ketut Gede; Young, Bruce (Faculty of Animal Science, Universitas Brawijaya, 2022)
Studies in young goats showed that feeding different N supplements did not significantly affect growth rate, rumen digestion, or N metabolism. It is unclear whether this finding is also applicable to lactating dairy goats. This study aimed to evaluate the efficacy of combinations of barley meal with soybean meal, cottonseed meal, or urea in high energy concentrate on nutrient digestion, milk-feed efficiency, milk production, and Nitrogen balance in dairy goats fed on barley hay as a basal diet. Four isoenergetic and isonitrogenous concentrate with different N sources were formulated and fed on lactating Saanen goats in a 4 x 4 Latin square design. The results showed that lactating Saanen goats producing 1.3 to 1.5 litre of milk per day and fed on a concentrate containing 1.7 % N in a high energy diet capable to sustain similar milk protein and N balance as that given concentrate with 2.2 % dietary N. Total nutrient intakes, nutrient digestion, milk-feed efficiency and milk production lactating Saanen goats was not affected by the source of dietary N. The results indicate that including urea in a supplement can maintain a similar level of milk yield, milk protein and milk efficiency in goats as can the feeding of more expensive soybean and cottonseed meals provided there is sufficient readily available dietary energy.